2016
DOI: 10.1038/srep29945
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 and RAB7L1 coordinately regulate axonal morphology and lysosome integrity in diverse cellular contexts

Abstract: Leucine-rich repeat kinase 2 (LRRK2) has been linked to several clinical disorders including Parkinson’s disease (PD), Crohn’s disease, and leprosy. Furthermore in rodents, LRRK2 deficiency or inhibition leads to lysosomal pathology in kidney and lung. Here we provide evidence that LRRK2 functions together with a second PD-associated gene, RAB7L1, within an evolutionarily conserved genetic module in diverse cellular contexts. In C. elegans neurons, orthologues of LRRK2 and RAB7L1 act coordinately in an ordered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(139 citation statements)
references
References 53 publications
9
128
0
Order By: Relevance
“…Genetic investigations in Caenorhabditis elegans neurons revealed that the RAB29 (GLO‐1) orthologue acts upstream of LRRK2 (LRK‐1) in a signaling pathway controlling axon termination (Kuwahara et al , ). It was also reported that Rab29 and LRRK2 double‐knockout mice exhibit an enlarged kidney phenotype that was non‐additive, relative to single Rab29 or LRRK2 knockout, further implying that these genes act in a common pathway (Kuwahara et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic investigations in Caenorhabditis elegans neurons revealed that the RAB29 (GLO‐1) orthologue acts upstream of LRRK2 (LRK‐1) in a signaling pathway controlling axon termination (Kuwahara et al , ). It was also reported that Rab29 and LRRK2 double‐knockout mice exhibit an enlarged kidney phenotype that was non‐additive, relative to single Rab29 or LRRK2 knockout, further implying that these genes act in a common pathway (Kuwahara et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…These association studies suggest that LRRK2 and Rab GTPases may interact in the pathogenesis of PD. Interestingly, Rab7L1 -deficient mice share similar kidney phenotypes and lysosomal defects as LRRK2 −/− mice, providing further support for a functional connection between LRRK2 and Rab proteins (Kuwahara et al, 2016). Future studies will be needed to elucidate how LRRK2 interacts with RAB7L1 and other Rab proteins in the regulation of the autophagy-lysosomal pathways.…”
Section: Discussionmentioning
confidence: 76%
“…Further supporting the idea that LRRK2 and Rabs co-operate to modulate vesicular trafficking, Rab7L1 KO mice have the same lysosomal pathology in the kidneys as LRRK2 KO mice and the combined deficiency of both proteins also results in a similar phenotype suggesting a genetic interaction with consistent direction between these two proteins [78]. Whether this is true for other Rabs that are direct substrates of LRRK2 is not known, and future studies are required to further substantiate the relationship between LRRK2, Rabs and regulation of the autophagy-lysosome system.…”
Section: A Physiological Role For Lrrk2 At Vesicular Membranesmentioning
confidence: 81%
“…Furthermore, cellular work showed that LRRK2 interacts with AP-3 as a downstream effector, essential for trafficking of lysosomal membrane proteins from the Golgi to the lysosomes [78]. The Drosophila homolog of LRRK2 (dLrrk) colocalizes with endosomes and lysosomes and interacts late endosomal protein Rab7.…”
Section: A Physiological Role For Lrrk2 At Vesicular Membranesmentioning
confidence: 99%